2006
DOI: 10.1526/003601106777789837
|View full text |Cite
|
Sign up to set email alerts
|

Highways and Population Change*

Abstract: In this paper we return to an issue often discussed in the literature regarding the relationship between highway expansion and population change. Typically it simply is assumed that this relationship is well established and understood. We argue, following a thorough review of the relevant literature, that the notion that highway expansion leads to increased population growth in the vicinity of the improved infrastructure finds only weak and often conflicting support. Using data on all major highway expansions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 20 publications
1
52
0
Order By: Relevance
“…On this large scale the driving forces to increase sprawl were population growth, early public transport infrastructure and decentralized employment. These results were also confirmed by Baum-Snow (2007) and Voss and Chi (2006), who estimated the effects of highways on population growth. For example, Baum-Snow (2007) showed that an additional highway crossing an US city results in a population decline in the core city and doubles the number of people relocating from the core of the city to the suburbs.…”
Section: Literature Reviewsupporting
confidence: 71%
See 1 more Smart Citation
“…On this large scale the driving forces to increase sprawl were population growth, early public transport infrastructure and decentralized employment. These results were also confirmed by Baum-Snow (2007) and Voss and Chi (2006), who estimated the effects of highways on population growth. For example, Baum-Snow (2007) showed that an additional highway crossing an US city results in a population decline in the core city and doubles the number of people relocating from the core of the city to the suburbs.…”
Section: Literature Reviewsupporting
confidence: 71%
“…Numerous disquisitions cover theoretical discussions (Mieszkowski and Mills 1993;Brake et al 2001;Johnson 2001;Carruthers and Ulfarsson 2003;Glaeser and Kahn 2004), methodical approaches (Loibl and Toetzer 2003;Herold et al 2005;Torrens 2006Torrens , 2008 and case studies (Ning and Yan 1995;Wang and Zhou 1999;Feng and Zhou 2005;Burchfield et al 2006;Voss and Chi 2006;Lee 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant factors include residential preference, highways, traffic volume, distance to access highways, journey to work, local capital expenditures on transportation, etc. (BARTEL, 1979;BROWN et al, 1997;FUGUITT and BROWN, 1990;SMITH et al, 2000;VOSS and CHI, 2006).…”
Section: Explanatory Variables Related To Population Growthmentioning
confidence: 99%
“…Adjustment of boundary changes at a small-area scale (e.g., MCD) often results in the zoning effect (Tolnay et al 1996;Voss and Chi 2006), as different approaches for adjustments might change the data analysis results dramatically. The data example below is aggregated at the MCD level, which consists of nonnested, mutually exclusive and exhaustive political territories.…”
Section: The Modifiable Areal Unit Problemmentioning
confidence: 99%
“…One is a data-driven approach, which tests for lack of spatial error autocorrelation after fitting a spatial lag model, and then tests for lack of spatial lag autocorrelation after fitting a spatial error model. In a study examining population growth, Voss and Chi (2006) find that the data-driven approach can help Spatial Regression Models for Demographic Analysis 31 determine which specification is the better model for accounting for the spatial autocorrelation. The other is a theory-based approach, which suggests that the choice between the spatial lag model and the spatial error model should be based on substantive grounds (Doreian 1980).…”
Section: Model Evaluationmentioning
confidence: 99%